Local Section News (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
MONTANA SECTION FREDERICK LAIST, Chairman F. W. BACORN, Vice-chairman E. B. YOUNG, Secretary-Treasurer, 52G Hennesy Building, Butte, Mont. C. H. CLAPP C. D. DEMOND The Montana Section held its annual meeting at the Silver Bow Club, Butte, Mont., on Friday, Feb. 7. The technical session was preceded by a dinner at which 54 members and guests were seated. N. B. Braly presided at the dinner and the, business and technical sessions. The officers whose names are noted above were elected for the ensuing year. H. B. Pulsifer presented a paper on The Metallurgy of Aluminum and Magnesium; it was discussed by C. H. Clapp and F. A. Linforth. J. C: Horgan presented a paper on The Manufacture of High Explosives and their Use in Metal Mines; it was discussed by C. W. Morse, J. J. Carrigan, and C. W. Goodale. The matter of reformed spelling as proposed in a circular letter coming from Palo Alto, Calif., was discussed, after which the Secretary was instructed to write to Secretary Stoughton and ask that when the matter is opened for discussion in New York he present the emphatic protest of the Montana Section against the alleged reforms in spelling. E. B. YOUNG, Secretary.